Fulminant hepatorenal syndrome due to Acetaminophen toxicity: A case report. Issue 5 (24th March 2021) - Nekoukar, Zahra; Moghimi, Minoo; Zakariaei, Zakaria; Fakhar, Mahdi; Tabaripour, Rabeeh
Abstract: HRS is a rare and poor prognosis complication of chronic acetaminophen toxicity, which presents by progressive decline in renal function secondary to liver failure. Abstract : HRS is a rare and poor prognosis complication of chronic acetaminophen toxicity, which presents by progressive decline in renal function secondary to liver failure.